Family-school cooperation in the context of inclusion of children with special educational needs - Rodrigues, Florbela Batista (2015)
Although current legislative measures recognize parents participation in school life, several difficulties remain and many barriers need to be broken down as there are still uncomfortable situations to be dealt with between school and parents. In this context, the aim of this study is to identify and to interpret parents, teachers and students’ opinions concerning parental involvement and participation in their children's school life. This study was carried out in an interpretative and descriptive paradigm which involves children with Special Educational Needs (SEN), their families and the relationship between them and the schools their children are attending. It is a exploratory, cross-sectional study, with convenience sample of 119 parents, 22 kindergarten teachers and teachers and 168 students attending a school situated in a rural area in the interior centre of Portugal. The four instruments used were adapted from Zenhas, A. (2006) and Dias, J. (1999). The results were analyzed through a descriptive statistics program, SPSS 19.0, which allowed us to discover that parents’ participation in their children's school life is still very incipient. The conclusion that it is up to school to assume a relevant role in coordinating with the families, to outline the objectives of the intervention and which strategies should be adopted to enable the increasing level of participation of families and implement policy measures where all stakeholders (parents, students with special educational needs and teachers) feel more included.